(untitled) (Hoboken, NJ, 2008)
This title is devoted to presenting some of the most important concepts and techniques for describing real-time systems and analyzing their behavior in order to enable the designer to achieve guarantees of temporal correctness. Topics addressed include mathematical models of real-time systems and associated formal verification techniques such as model checking, probabilistic modeling and verification, programming and description languages, and validation approaches based on testing. With contributions from authors who are experts in their respective fields, this will provide the reader with the state of the art in formal verification of real-time systems and an overview of available software tools.
Keywords: Real-time data processing,Computer software,Formal methods (Computer science),Xử lý dữ liệu tại chỗ,Phần mềm máy tính,Phương pháp chính ( khoa học vi tính ); Verification,Xác minh